Member - Chrysostomou, Christis (My University, 2026)
The seven-member Committee studied the existing condition of the Cyprus Education System from kindergarten to university level and made reform proposals. The proposals of the committee such as the whole-day school, the unification of the high school final exams with the university entrance exams, the teacher’s assessment system etc., have started to materialize.